Influence Of The Inverter Boost Voltage On The Transients Of Variable Speed Drive - Rinkevičienė, R.; Batkauskas, V. (Elektronika ir Elektrotechnika, 2009)
Method and apparatus for providing adequate breakaway torque for the a-c motors started in a system in which inverter supplies electric power to the motors are presented. The output voltage of the source is substantially increased for an initial predetermined starting period to provide adequate breakaway torque, the voltage thereafter being reduced to a level corresponding to a predetermined desired constant ratio relative to output frequency. Systems with a static load with and without the starting voltage boost are analyzed. Different output frequencies are used to find out the optimal relation between voltage and frequency in scalar control method especially low speed region. Ill. 9, bibl. 7 (in English; summaries in English, Russian and Lithuanian)